A land controlled‐source electromagnetic experiment using a deep vertical electric dipole: experimental settings, processing, and first data interpretation. (November 2015) - Vilamajó, E.; Rondeleux, B.; Queralt, P.; Marcuello, A.; Ledo, J.
ABSTRACT: A multichannel borehole‐to‐surface controlled‐source electromagnetic experiment was carried out at the onshore CO2 storage site of Hontomín (Spain). The electromagnetic source consisted of a vertical electric dipole located 1.5 km deep, and the electric field was measured at the surface. The subsurface response has been obtained by calculating the transfer function between the transmitted signal and the electric field at the receiver positions. The dataset has been processed using a fast processing methodology, appropriate to be applied on controlled‐source electromagnetics (CSEM) data with a large signal‐to‐noise ratio. The dataset has been analysed in terms of data quality and repeatability errors, showing data with low experimental errors and good repeatability. We evaluate if the induction of current along the casing of the injection well can reproduce the behaviour of the experimental data.